Hydrogen Leakage Diagnosis for Proton Exchange Membrane Fuel Cell Systems: Methods and Suggestions on Its Application in Fuel Cell Vehicles - Ying Tian; Qiang Zou; Zezhao Lin (IEEE Access, 2020)
Proton exchange membrane fuel cell vehicles using hydrogen as fuel has become one of the key development directions in the field of new energy vehicles. However, hydrogen is flammable, it is easy to trigger serious safety accidents once hydrogen leak occurs. Therefore, the application of hydrogen leakage diagnosis methods is essential for the safe operation of proton exchange membrane fuel cell system. This paper reviews the existing methods of diagnosing hydrogen leakage for proton exchange membrane fuel cell system. The principles, research status and application scopes of different methods are elaborated, and these methods are analyzed based on three aspects of on-line diagnosis, real-time performance and calculation complexity. Furthermore, suggestions are provided for the selection of on-line hydrogen leakage diagnosis methods for fuel cell vehicles. Based on this review, readers can easily understand the current status of hydrogen leakage diagnosis methods for proton exchange membrane fuel cell system, and it can provide references for the application selection of the hydrogen leakage diagnosis methods for fuel cell vehicles.